Safety and efficacy of a feed additive consisting of l‐threonine (produced with Escherichia coli CGMCC 7.455) for all animal species (Kempex Holland B.V.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of the feed additive consisting of l‐threonine produced by fermentation with Escherichia coli CGMCC 7.455 when used as a nutritional additive in feed and water for drinking for all animal species and categories. The production strain is genetically modified. None of the introduced genetic modifications raised a safety concern. Viable cells of the production strain and its DNA were not detected in the final additive. Therefore, the final product does not give raise to any safety concern regarding the genetic modification of the production strain. The use of l‐threonine (≥ 98.5%) produced with E. coli CGMCC 7.455 to supplement feed is safe for the target species. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) has concerns on the safety of the simultaneous oral administration of l‐threonine via water for drinking and feed due to possible amino acid imbalances and hygienic reasons. The use of l‐threonine produced with E. coli CGMCC 7.455 in animal nutrition raises no safety concerns to consumers of animal products and to the environment. In the absence of data, the FEEDAP Panel cannot conclude on the potential of the additive to be irritant to skin or eyes, or on its potential to be a dermal sensitiser. The endotoxin activity in the additive does not pose a risk for the user via inhalation. The additive l‐threonine is regarded as an effective source of the amino acid l‐threonine for all non‐ruminant species. In order to be as efficacious in ruminants as in non‐ruminants, it should be protected from ruminal degradation.